2020
DOI: 10.4274/tjh.galenos.2020.2019.0459
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study on prevalence, specificity, sex and age distribution of alloimmunization in two general hospitals in Athens

Abstract: Objective: Blood transfusion is a common lifesaving treatment but it is often complicated with alloimmunization. Previously studies in Greece have concentrated on alloimmunization in multiply transfused thalassemic patients or antenatal women. However, the relative frequency of red blood cell (RBC) alloantibodies in the general patient population has not been studied so far. The aim of the present retrospective study was to estimate the prevalence and specificity of RBC alloantibodies in a large c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…The most common antibodies from this category are antibodies against high-specificity antigens from the blood group system Rh (anti-D, anti-c, anti-C and anti-E) and Kell ( 5 , 6 ). Their clinical importance is reflected in the fact that in the optimal environment of the bloodstream in-vivo they react very quickly with the appropriate antigens on the recipient’s erythrocytes and may lead to an acute hemolytic reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common antibodies from this category are antibodies against high-specificity antigens from the blood group system Rh (anti-D, anti-c, anti-C and anti-E) and Kell ( 5 , 6 ). Their clinical importance is reflected in the fact that in the optimal environment of the bloodstream in-vivo they react very quickly with the appropriate antigens on the recipient’s erythrocytes and may lead to an acute hemolytic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…According to Erikstein et al, anti-E antibody was also identified as the most common antibody in Norway (20 %), followed by anti-M (18 %), anti-K (10 %), and anti-D (9 %) ( 10 ). In a study conducted by Politou et al in three Greek hospitals on a sample of 53,800 patients who were transfused from 2012 to 2016, the antibody with the highest frequency was anti-K (26,61%), followed by anti-E (16,02%), anti-D (15,02%), anti-Jka (5,87%) and anti-M antibody (5,72%) ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of RBC alloimmunization during pregnancy occurs when the fetus inherits a different set of RBC antigens than the mother. For example, if the mother is RhD-negative and the fetus is RhD-positive, the mother's immune system may produce antibodies against the fetal Rh antigens, recognizing them as foreign [ 9 ]. The Rh antigen (D, C, c, E) is one of the RBC antigens that frequently engage in RBC alloimmunization during pregnancy [ 9 ].…”
Section: Reviewmentioning
confidence: 99%
“…The reported rate of alloimmunization in the general population ranges from 0.46% to 2.4% [ 9 ]. Besides pregnancy, patients who received transfusions are among the most affected by alloimmunization.…”
Section: Reviewmentioning
confidence: 99%
“…The reported range may be explained by genetic heterogeneity between the donor and recipient populations, variations in transfusion practices, and variations in the specificity and sensitivity of the test methodologies [27]. It is recommended that preemptive antigen matching for Rh (C, c, E, e) and K be performed on oncology patients and women of reproductive age to prevent alloimmunization and increase transfusion safety by lowering alloantibody formation [23].…”
Section: Introductionmentioning
confidence: 99%